Palladium‐Catalyzed Route to Three‐Component, One‐Pot Sequential Synthesis of Functionalized Cyclazines: 2, 2a1, 4‐Triazacyclopenta[cd]indenes. Issue 10 (12th July 2013) - Yang, Anjiang; Jiang, Ruwei; Khorev, Oleg; Yu, Ting; Zhang, Yongliang; Ma, Lanping; Chen, Guohua; Shen, Jingkang; Meng, Tao
Abstract An efficient tandem route to the synthesis of 2, 2a1, 4‐triazacyclopenta[cd]indene derivatives of the cyclazine family has been developed. The target compounds were obtained in moderate to good yields by an ytterbium(III) triflate/palladium(II) acetate‐catalyzed three‐component domino reaction involving a palladium‐catalyzed intramolecular α‐arylation of an α‐aminocarbonyl functionality. This in turn will set the stage for a wide application of this useful reaction for the synthesis of structurally diverse polyheterocyclic skeletons containing the privileged imidazo[1, 2‐a]pyridine structure.